Manufacturing method of solid electrolyte material and argyrodite type sulfide solid electrolyte particle

By mixing a sulfide with lithium, phosphorus, and sulfur, and using a solid carbon source, the method enhances the electronic conductivity and structural stability of solid electrolytes in lithium-ion batteries, addressing conductivity issues and improving battery performance.

JP2025003249APending Publication Date: 2025-01-09NICHIA CORP

Patent Information

Application Number
JP2023118415
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-23
Filing Date
2023-07-20
Publication Date
2025-01-09

AI Technical Summary

Technical Problem

Existing solid electrolytes in all-solid-state lithium-ion secondary batteries lack sufficient electronic conductivity, necessitating the addition of conductive additives, and existing methods for improving conductivity are either inefficient or require high temperatures that can destabilize the electrolyte structure.

Method used

A method involving the mixing of a sulfide with lithium, phosphorus, and sulfur having an argyrodite crystal structure with a solid carbon source, followed by heat treatment at controlled temperatures to create a solid electrolyte material with enhanced electronic conductivity, utilizing a carbon source that maintains the electrolyte's structure.

Benefits of technology

The method produces a solid electrolyte material with high electronic conductivity and structural stability, enabling improved battery performance through reduced resistance and enhanced charge/discharge capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025003249000003
    Figure 2025003249000003
  • Figure 2025003249000004
    Figure 2025003249000004
  • Figure 2025003249000005
    Figure 2025003249000005
Patent Text Reader

Abstract

To provide a solid electrolyte material having high electron conductivity and a manufacturing method thereof.SOLUTION: A manufacturing method of a solid electrolyte material includes: mixing a sulfide having an argyrodite type crystal structure including lithium, phosphor and sulfur, with a carbon source being solid at a normal state, to obtain a mixture; and applying a heat treatment to the mixture at temperature 400°C to 550°C, inclusive.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for producing a solid electrolyte material, and argyrodite-type sulfide solid electrolyte particles. [Background technology]

[0002] All-solid-state lithium-ion secondary batteries that use solid electrolytes as electrolytes have been attracting attention. The positive and negative electrodes of all-solid-state lithium-ion secondary batteries contain a certain amount of solid electrolyte, but since solid electrolytes are not conductive, it is necessary to add a conductive additive at the same time. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2012 / 164724 [Patent Document 2] JP 2020-135947 A Summary of the Invention [Problem to be solved by the invention]

[0004] An object of one aspect of the present disclosure is to provide a solid electrolyte material having high electronic conductivity and a method for producing the same. [Means for solving the problem]

[0005] A first aspect of the present disclosure is a method for producing a mixture comprising: mixing a sulfide containing lithium, phosphorus, and sulfur and having an argyrodite-type crystal structure with a carbon source that is solid at standard conditions to obtain a mixture; heat treating the mixture at a temperature of 400° C. or more and 550° C. or less; The present invention relates to a method for producing a solid electrolyte material comprising the steps of:

[0006] A second aspect of the present disclosure is a sulfide containing lithium, phosphorus, and sulfur and having an argyrodite-type crystal structure, at least a portion of which contains a carbon material, and having a peak intensity of D band measured by Raman spectroscopy of I D , the G band peak intensity is I G , 415cm -1 More than 430cm -1 The peak intensity in the following region is I A When I G / I D is 0.8 or more, and I G / I A is 0.07 or more. Effect of the Invention

[0007] According to one aspect of the present disclosure, it is possible to provide a solid electrolyte material having high electronic conductivity and a method for producing the same. [Brief description of the drawings]

[0008] [Figure 1] 1 is a cross-sectional view showing a schematic configuration of a battery 1000. [Diagram 2] 1 is an X-ray diffraction pattern of a solid electrolyte material according to Example 1. [Diagram 3] 1 is an X-ray diffraction pattern of a solid electrolyte material according to a reference example. [Figure 4] 2 is an X-ray diffraction pattern of a solid electrolyte material according to Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] In this specification, the term "step" includes not only an independent step, but also a step that cannot be clearly distinguished from other steps, as long as the intended purpose of the step is achieved. Furthermore, the content of each component in the composition means the total amount of the multiple substances present in the composition, unless otherwise specified, when multiple substances corresponding to each component are present in the composition. Furthermore, the upper and lower limits of the numerical ranges described in this specification can be arbitrarily selected and combined. Hereinafter, embodiments of the present invention will be described in detail. However, the embodiments shown below are examples of solid electrolyte materials, their manufacturing methods, and batteries for embodying the technical ideas of the present invention, and the present invention is not limited to the solid electrolyte materials, their manufacturing methods, and batteries shown below.

[0010] (Method of manufacturing solid electrolyte material) The method for producing a solid electrolyte material according to the present disclosure includes the steps of: Mixing a sulfide containing lithium, phosphorus, and sulfur and having an argyrodite-type crystal structure with a carbon source that is solid at a standard state to obtain a mixture; heat treating the mixture at a temperature of 400° C. or more and 550° C. or less; Includes.

[0011] In the method for producing a solid electrolyte material according to the present disclosure, a sulfide having an argyrodite-type crystal structure and a carbon source that is solid under standard conditions are mixed and used, thereby improving the electronic conductivity of the resulting solid electrolyte material. This is believed to be because the solid electrolyte material is coated with carbon. In addition, by using a solid carbon source as the carbon source, heat treatment can be performed at a relatively low temperature and in a simple process, and the collapse of the argyrodite-type sulfide solid electrolyte material can be suppressed.

[0012] (preparation process) In the preparation step, a sulfide containing lithium, phosphorus and sulfur and having an argyrodite-type crystal structure is obtained.

[0013] First, a mixture containing a compound containing lithium, a compound containing phosphorus and a compound containing sulfur is obtained. The mixture may further contain a compound containing chlorine. The mixture may further contain a metal sulfate and a metal phosphate. The mixture may be, for example, a raw material composition of a solid electrolyte material.

[0014] Lithium-containing compounds include lithium sulfide (e.g., Li 2 S), lithium oxide (e.g., Li 2 O), lithium carbonate (e.g., Li 2 CO 3 ), lithium hydroxide (LiOH), etc., and the electrolyte may contain at least one selected from the group consisting of these, and preferably contains at least lithium sulfide.

[0015] The content of the lithium-containing compound in the mixture may be, for example, 3 to 7 moles, preferably 3.1 to 5 moles, more preferably 3.3 to 4.3 moles, per mole of the phosphorus- and sulfur-containing compound. The content of the lithium-containing compound does not include metal sulfates, metal phosphates, and compounds containing chlorine, which will be described later.

[0016] The phosphorus and sulfur containing compound may be, for example, a compound having a phosphorus-sulfur bond. Examples of the phosphorus and sulfur containing compound include phosphorus trisulfide (e.g., P 2 S 3 ), diphosphorus pentasulfide (e.g., P 2 S 5 ) and the like, and the compound may contain at least one selected from the group consisting of these, and preferably contains at least diphosphorus pentasulfide.

[0017] The metal sulfate may be, for example, an alkali metal sulfate. Examples of metal sulfates include lithium sulfate (e.g., Li 2 SO 4 ), sodium sulfate (Na 2 SO 4) and the like can be mentioned, and at least one selected from the group consisting of these may be included, and preferably at least lithium sulfate may be included.

[0018] When the mixture contains a metal sulfate, the content of the metal sulfate in the mixture may be, for example, 1.0% by mass or less, preferably 0.7% by mass or less, 0.6% by mass or less, or 0.55% by mass or less, based on the mixture. The lower limit of the content of the metal sulfate may be, for example, 0.01% by mass or more, preferably 0.1% by mass or more, 0.2% by mass or more, or 0.4% by mass or more, based on the mixture. When the content of the metal sulfate is within the above range, the lithium ion conductivity of the produced solid electrolyte material is improved, the battery resistance is reduced, and the battery characteristics tend to be improved.

[0019] The metal phosphate may be, for example, an alkali metal phosphate. Examples of the metal phosphate include lithium phosphate (e.g., Li 3 PO 4 ), Sodium phosphate (Na 3 PO 4 ) and the like, and the lithium phosphate may contain at least one selected from the group consisting of these, and preferably contains at least lithium phosphate.

[0020] When the mixture contains a metal phosphate, the content of the metal phosphate in the mixture may be, for example, 15.0% by mass or less, preferably 10.0% by mass or less, 7.0% by mass or less, 5.0% by mass or less, or 3.0% by mass or less, based on the mixture. The lower limit of the content of the metal phosphate may be, for example, 0.1% by mass or more, preferably 0.5% by mass or more, or 1.0% by mass or more, based on the mixture. When the content of the metal phosphate is within the above range, the battery resistance of the solid electrolyte material produced tends to be further reduced.

[0021] The chlorine-containing compound may be, for example, a metal chloride, preferably an alkali metal chloride. Examples of the alkali metal include lithium (Li), sodium (Na), potassium (K), and rubidium (Rb). Specific examples of the chlorine-containing compound include lithium chloride (e.g., LiCl), sodium chloride (e.g., NaCl), and potassium chloride (e.g., KCl), and may include at least one selected from the group consisting of these compounds, and may preferably include at least lithium chloride.

[0022] The content of the chlorine-containing compound in the mixture may be, for example, 0 to 3.9 moles, preferably 1 to 3.7 moles, more preferably 2.9 to 3.5 moles, relative to 1 mole of the phosphorus- and sulfur-containing compound. When the content of the chlorine-containing compound in the mixture is within the above range, the effect of reducing the internal resistance described below tends to be greater.

[0023] A part of the compound containing chlorine may be replaced by a compound containing bromine. The compound containing bromine may be, for example, a metal bromide, preferably an alkali metal bromide. Examples of the alkali metal include lithium (Li), sodium (Na), potassium (K), and rubidium (Rb). Specific examples of the compound containing bromine include lithium bromide (for example, LiBr), sodium bromide (for example, NaBr), and potassium bromide (for example, KBr), and may contain at least one selected from the group consisting of these, and may preferably contain at least lithium bromide. When a part of the compound containing chlorine is replaced by a compound containing bromine, the content of the compound containing bromine may be, for example, 0 mole or more and 3.9 moles or less, preferably 1 mole or more and 3.7 moles or less, and more preferably 2.9 moles or more and 3.5 moles or less, relative to 1 mole of the compound containing phosphorus and sulfur. In addition, when a part of the chlorine-containing compound is replaced with a bromine-containing compound, the total amount of the chlorine-containing compound and the bromine-containing compound may be 0 mole or more and 3.9 moles or less, preferably 1 mole or more and 3.7 moles or less, and more preferably 2.9 moles or more and 3.5 moles or less, relative to 1 mole of the phosphorus- and sulfur-containing compound.

[0024] In the mixture, a part of the compound containing chlorine may be replaced by a compound containing a halogen atom other than chlorine and bromine. Examples of the halogen atom contained in the compound containing a halogen atom other than chlorine and bromine include fluorine and iodine, and at least one of them may be contained. The compound containing a halogen atom other than chlorine and bromine may contain, for example, a metal halide, preferably an alkali metal halide, and may contain at least a lithium halide.

[0025] When the mixture contains a compound containing a halogen atom other than chlorine and bromine, the content of the compound containing a halogen atom other than chlorine and bromine in the mixture may be, for example, greater than 0 mol and less than 0.1 mol, preferably greater than 0 mol and less than 0.05 mol, per 1 mol of the compound containing chlorine.

[0026] The mixture can be prepared by weighing and mixing the lithium-containing compound, the phosphorus- and sulfur-containing compound, the metal sulfate, the metal phosphate, and, if necessary, the chlorine-containing compound so as to have a desired content. For example, the total molar content ratio of the lithium-containing compound and the chlorine-containing compound to the phosphorus- and sulfur-containing compound in the mixture may be, for example, 3 or more and 8 or less, preferably 5 or more and 7.8 or less, and more preferably 6 or more and 7.5 or less.

[0027] Examples of a method for mixing the raw materials include a mixing method capable of applying mechanical stress, such as a high-speed shear mixer, a ball mill, a bead mill, a vibration mill, or a planetary ball mill.

[0028] The mixture obtained above is heat-treated to obtain a heat-treated product. The heat-treated product contains a sulfide that contains lithium, phosphorus, and sulfur and has an argyrodite-type crystal structure, and the sulfide having the argyrodite-type crystal structure may contain a crystalline phase. When the sulfide contains a crystalline phase, Li 7 P.S. 6 The composition may include a crystalline phase having a composition represented by the formula:

[0029] The heat treatment temperature of the mixture may be, for example, 400°C or higher, preferably 450°C or higher, or 500°C or higher. The heat treatment temperature may be, for example, lower than 700°C, preferably 650°C or lower, or 600°C or lower. If the heat treatment temperature is higher than the above range, the argyrodite-type crystal structure may be partially destroyed. The heat treatment time may be, for example, 1 hour or more and 20 hours or less, preferably 2 hours or more and 15 hours or less. The heat treatment atmosphere may be, for example, an inert gas atmosphere such as nitrogen gas or rare gas, or the heat treatment may be performed under reduced pressure.

[0030] By the above heat treatment, a sulfide containing lithium, phosphorus and sulfur and having an argyrodite-type crystal structure is obtained.

[0031] (Mixing with carbon source) In the step of mixing with a carbon source, a sulfide containing lithium, phosphorus, and sulfur and having an argyrodite-type crystal structure is mixed with a carbon source that is solid under standard conditions to obtain a mixture.

[0032] Here, the standard condition is 25°C and 10 5 It means the state of Pa.

[0033] The solid carbon source may be, for example, a hydrocarbon. Such a hydrocarbon preferably does not have a double bond in its structure. When the hydrocarbon carbon source does not have a double bond, the resulting solid electrolyte material contains fewer impurities. Therefore, it is easier to achieve higher electronic conductivity.

[0034] The hydrocarbon may be a hydrocarbon having 10 to 60 carbon atoms, for example, a hydrocarbon having 12 to 40 carbon atoms. In one embodiment, the hydrocarbon may be a saturated hydrocarbon having 10 to 40 carbon atoms, or a saturated hydrocarbon having 12 to 36 carbon atoms. In another embodiment, the hydrocarbon may be an unsaturated hydrocarbon having 10 to 40 carbon atoms, or an unsaturated hydrocarbon having 16 to 40 carbon atoms. The hydrocarbon may be linear or cyclic, or may have both a linear structure and a cyclic structure.

[0035] Examples of the above-mentioned hydrocarbons include octadecane, eicosane, henicosane, docosane, tricosane, tetracosane, pentacosane, hexacosane, heptacosane, octacosane, nonacosane, triacontane, hentriacontane, dotriacontane, tetratriacontane, pentatriacontane, hexatriacontane, heptatriacontane, octatriacontane, nonatriacontane, tetracontane, dotetracontane, tetratetracontane, pentacontane, tetrapentacontane, cyclododecane, cyclotetradecane, cyclopentadecane, hexadecahydropyrene, norbornane, endo-tetrahydrodicyclopentadiene, adamantane, diamantane, β-carotene, lycopene, polyethylene, etc. Among them, hexatriacontane, eicosane, cyclododecane, or β-carotene is preferably used.

[0036] The mixing ratio of the sulfide to the carbon source in the mixture may be, for example, 100:1 to 60:40, preferably 98:2 to 70:30, more preferably 98:2 to 80:20, for example, 90:10 to 80:20, in terms of mass ratio. By setting the mixing ratio of the sulfide to the carbon source in the mixture to the above range, the electronic conductivity of the obtained solid electrolyte material may be further improved.

[0037] (Heat treatment process) In the heat treatment step, the mixture obtained in the step of mixing with the carbon source is heat treated at a temperature of 400° C. or higher and 550° C. or lower.

[0038] The heat treatment temperature is 400° C. or more, and may be preferably 430° C. or more, 450° C. or more, or 460° C. or more. The heat treatment temperature is 550° C. or less, and may be preferably 520° C. or less, 500° C., or 480° C. or less.

[0039] The duration of the heat treatment may be, for example, from 0.5 hours to 12 hours, preferably from 1 hour to 6 hours, or from 2 hours to 5 hours.

[0040] The atmosphere for the heat treatment may be, for example, an inert gas atmosphere such as nitrogen gas or a rare gas, or the heat treatment may be performed under reduced pressure. The heat treatment is preferably performed in a closed atmosphere.

[0041] (Argyrodite-type sulfide solid electrolyte material) An argyrodite-type sulfide solid electrolyte material (hereinafter, simply referred to as "solid electrolyte material") is a sulfide that contains lithium, phosphorus, and sulfur and has an argyrodite-type crystal structure, at least a part of which contains a carbon material, and has a D band peak intensity of I D , the G band peak intensity is I G , 415cm -1 More than 430cm -1 The peak intensity in the following region is I A When I G / ID is 0.8 or more, and I G / I A The peak at 415 cm due to the crystal structure of the argyrodite-type sulfide solid electrolyte material is 0.07 or more. -1 More than 430cm -1 As confirmed in the following areas, I G / I A is considered to be an index representing the amount of graphite in the solid electrolyte material. In this specification, the peak intensity ratio in Raman spectroscopy is determined not by the area ratio but by the ratio of the maximum peak heights in a predetermined region.

[0042] Argyrodite-type sulfide solid electrolyte material is I G / I D is 0.8 or more, and I G / I A By exhibiting a Raman spectrum with a Raman coefficient of 0.07 or more, high electronic conductivity is exhibited.

[0043] I G / I D is an index showing the degree of graphitization of carbon. The higher the index, the higher the electronic conductivity of the solid electrolyte material. G / I D is 0.8 or greater, and may be, for example, 0.9 or greater, 1.0 or greater, or 1.1.

[0044] I G / I A is an index showing the ratio of electronically conductive carbon to the solid electrolyte, and the higher it is, the higher the electronic conductivity of the solid electrolyte material is. G / I A is 0.07 or more, for example, 0.08 or more, preferably 0.1 or more, and more preferably 0.15 or more. G / I A In reality, it may be 0.3 or less.

[0045] The argyrodite-type sulfide solid electrolyte material was analyzed by Raman spectroscopy at 1800 cm -1 More than 4000cm -1 The maximum intensity in the following region is I BWhen I B / I A may be 0.20 or less, preferably 0.10 or less, more preferably 0.05 or less, and even more preferably 0.03 or less. B / I A In reality, it may be 0.001 or more. A peak at 1800 cm that is not attributable to either the crystal structure of the argyrodite-type sulfide solid electrolyte material or graphite -1 More than 4000cm -1 As confirmed in the following areas, I B / I A is considered to be an index representing the proportion of impurities contained in the solid electrolyte material.

[0046] Argyrodite-type sulfide solid electrolyte material is I B / I A When the Raman spectrum has a value in the above range, high electronic conductivity is exhibited.

[0047] In the measurement using X-ray diffraction, the argyrodite-type sulfide solid electrolyte material has a maximum intensity in the region of 29.5≦2θ≦30.5. A , the maximum intensity in the region of 33.5 ≦ 2θ ≦ 34.5 is X B When X A / X B It is preferable that the diffraction pattern exhibits a ratio of maximum intensity to maximum intensity in the X-ray diffraction method. In this specification, the maximum intensity ratio is not an area ratio but is determined by the ratio of maximum heights of peaks in a predetermined region.

[0048] Argyrodite-type sulfide solid electrolyte material is X A / X B The argyrodite-type crystal structure is highly maintained by having a diffraction pattern with a refractive index of ≦0.01. The argyrodite-type crystal structure can be maintained by avoiding exposure to high temperatures, for example, temperatures of 700° C. or higher.

[0049] The carbon material may be present at or near the surface of the argyrodite-type sulfide solid electrolyte material.

[0050] The carbon material means a material containing carbon atoms, and the form of existence is not particularly limited. The carbon material is preferably conductive. The presence of the carbon material can be confirmed by the presence of the G band or D band in the Raman spectrum.

[0051] The argyrodite-type sulfide solid electrolyte material contains a sulfide that contains lithium, phosphorus, and sulfur in its composition and has an argyrodite-type crystal structure. The sulfide that constitutes the solid electrolyte material is, for example, Li 7 P.S. 6 The sulfide may include a crystalline phase having a composition represented by the formula: 7 P.S. 6 The presence of a crystalline phase having a composition represented by the formula (I) can be confirmed, for example, by X-ray diffraction (XRD) measurement. Specifically, when XRD measurement is performed on a solid electrolyte material by the θ-2θ method using CuKα rays having wavelengths of 0.15405 nm and 0.15444 nm as an X-ray source, Li 7 P.S. 6 Peaks corresponding to a crystal phase having a composition represented by the formula (I) typically appear at 2θ=25.7°, 30.2°, 31.6°, 45.3°, 48.2°, and 52.7°.

[0052] The lithium content in the sulfide composition may be, for example, 4 to 7 moles, preferably 5 to 6 moles, per mole of phosphorus. The sulfur content in the sulfide composition may be, for example, 3 to 6 moles, preferably 4 to 5 moles, per mole of phosphorus.

[0053] The sulfide having an argyrodite crystal structure may contain a halogen in its composition. The inclusion of a halogen tends to further improve lithium ion conductivity. Examples of the halogen include chlorine, bromine, iodine, etc., and may contain at least one selected from the group consisting of these, may contain one of chlorine and bromine, or may contain at least chlorine. The inclusion of chlorine tends to result in a sulfide solid electrolyte with higher chemical stability.

[0054] When the sulfide having an argyrodite-type crystal structure contains a halogen in its composition, the content of the halogen in the sulfide composition may be, for example, more than 0 moles and not more than 2 moles per mole of phosphorus, preferably 1 mole or more and not more than 2 moles, and more preferably 1.4 moles or more and not more than 1.8 moles. When the halogen contained in the composition of the sulfide having an argyrodite-type crystal structure is in the above range, the lithium ion conductivity of the sulfide tends to be more easily improved.

[0055] The solid electrolyte material may contain lithium phosphate in addition to the sulfide having an argyrodite-type crystal structure. The presence of lithium phosphate in the solid electrolyte material can be evaluated using an X-ray diffraction pattern. Specifically, when the solid electrolyte material is subjected to XRD measurement by the θ-2θ method using CuKα rays with wavelengths of 0.15405 nm and 0.15444 nm as an X-ray source, lithium phosphate (for example, Li 3 PO 4 ) typically appear at 2θ=22.3°, 23.2°, 24.8°, 33.9°, and 36.6°.

[0056] In addition to sulfides having an argyrodite-type crystal structure, solid electrolyte materials containing lithium phosphate show lithium phosphate (e.g., Li 3 PO 4 ) and the first peak corresponding to Li 7 P.S. 6 The first peak may have a diffraction angle 2θ of 21° or more and less than 23°, and may be about 22.3°. The second peak may have a diffraction angle 2θ of 25° or more and less than 27°, and may be about 25.7°.

[0057] The content of lithium phosphate contained in the solid electrolyte material can be evaluated, for example, by using an X-ray diffraction pattern. Specifically, it can be evaluated by the ratio of the intensity of the first peak to the intensity of the second peak (hereinafter, also simply referred to as "peak intensity ratio"). The solid electrolyte material may have a ratio of the intensity of the first peak to the intensity of the second peak of, for example, 0.03 or more and less than 0.15, preferably 0.04 or more or 0.045 or more, and preferably 0.10 or less or 0.06 or less. When the peak intensity ratio corresponding to the content of lithium phosphate is within the above range, the battery resistance tends to be further reduced.

[0058] The solid electrolyte material may contain sulfate ions. The content of sulfate ions contained in the solid electrolyte material may be, for example, 0.5 mass% or more, and preferably 0.54 mass% or more, based on the solid electrolyte material. The upper limit of the content of sulfate ions may be, for example, 1.0 mass% or less, and preferably 0.8 mass% or less, based on the solid electrolyte material. When sulfate ions are present in a content within the above range, lithium ion conductivity is improved, battery resistance is reduced, and battery characteristics tend to be improved.

[0059] The content of sulfate ions in the solid electrolyte material is measured by high-frequency inductively coupled plasma atomic emission spectrometry (ICP atomic emission spectrometry).

[0060] The composition of the solid electrolyte material may be, for example, a composition ratio of lithium atoms of 4 to 7 moles, preferably 5 to 6 moles, relative to 1 mole of phosphorus. The composition ratio of sulfur atoms may be, for example, 3 to 6 moles, preferably 4 to 5 moles, relative to 1 mole of phosphorus. The composition ratio of oxygen atoms may be, for example, 0 to 4 moles, preferably 0.1 to 2.0 moles, relative to 1 mole of phosphorus. The composition ratio of halogen atoms may be, for example, 0 to less than 2 moles, preferably 1.4 to 1.8 moles, relative to 1 mole of phosphorus.

[0061] The solid electrolyte material may have a composition represented by the following formula (I), for example. Li r P.S. s O t X u (I) In formula (I), r, s, t, and u are 4≦r≦7, 3≦s≦6, 0≦t≦4, and 0≦u<2, respectively, and X may be at least one selected from the group consisting of F, Cl, Br, and I. Preferably, 5≦r≦6, 4≦s≦5, 0.1≦t≦2, and 1.4≦u≦1.8, and X may be at least one of Br and Cl.

[0062] (battery) The battery is configured to include an electrolyte containing the above-mentioned solid electrolyte material, a positive electrode, and a negative electrode. The electrolyte may form an electrolyte layer disposed between the positive electrode and the negative electrode. An example of the configuration of the battery will now be described with reference to the drawings. FIG. 1 is a cross-sectional view showing a schematic configuration of a battery 1000. The battery 1000 includes a positive electrode 201, a negative electrode 203, and an electrolyte layer 202 disposed between the positive electrode 201 and the negative electrode 203. The positive electrode 201 includes a positive electrode active material layer containing a positive electrode active material 204. The positive electrode active material layer constituting the positive electrode 201 may include a conductive assistant, a solid electrolyte material 100, and the like in addition to the positive electrode active material 204. The positive electrode 201 may also include a current collector and a lead connected to the current collector. The negative electrode 203 includes a negative electrode active material layer containing a negative electrode active material 205. The negative electrode active material layer constituting the negative electrode 203 may include a conductive assistant, a solid electrolyte material 100, and the like in addition to the negative electrode active material 205. The negative electrode 203 may include a current collector and a lead connected to the current collector. The electrolyte layer 202 includes a solid electrolyte material. An example of the battery is a lithium ion battery, which may be an all-solid-state secondary battery.

[0063] The lithium ion battery in this specification includes a lithium ion secondary battery using a lithium transition metal composite oxide in the positive electrode, and a lithium sulfur battery using a material that absorbs and releases lithium in the negative electrode. For specific examples of lithium transition metal composite oxides, reference can be made to, for example, paragraph 0066 of WO 2017 / 141735 (paragraphs 0152 to 0156 of U.S. Patent Publication No. 2018 / 0309167). For materials that absorb and release lithium, reference can be made to paragraph 0058 of WO 2015 / 056564 (paragraph 0070 of U.S. Patent Publication No. 2016 / 0254529).

[0064] For example, a lithium transition metal composite oxide is used for the positive electrode active material 204, and transition metal oxides having a layered rock salt structure and transition metal oxides having a spinel structure described in the above-mentioned publications can be used. In addition to lithium-containing transition metal phosphate compounds, lithium-containing transition metal halide phosphate compounds, and lithium-containing transition metal silicate compounds, transition metal fluorides, transition metal sulfides, transition metal oxyfluorides, transition metal oxysulfides, transition metal oxynitrides, and the like can also be used for the positive electrode active material 204. In the case of a lithium-sulfur battery, elemental sulfur can be used as the positive electrode active material.

[0065] The average particle size of the positive electrode active material 204 may be, for example, 0.1 μm or more and 30 μm or less. When the average particle size of the positive electrode active material 204 is 30 μm or less, lithium diffusion in the positive electrode active material 204 is not too slow, and the battery may operate more easily at high output. The thickness of the positive electrode active material layer may be, for example, 10 μm or more and 500 μm or less. When the thickness of the positive electrode active material layer is 10 μm or more, it may be easier to ensure sufficient energy density of the battery. Also, when the thickness of the positive electrode active material layer is 500 μm or less, it may be easier to operate at high output.

[0066] The average particle size of the positive electrode active material 204 may be larger than the average particle size of the solid electrolyte material 100. This allows the positive electrode active material 204 and the solid electrolyte material to be well dispersed in the positive electrode active material layer.

[0067] The volume ratio of the positive electrode active material 204 to the total volume of the positive electrode active material 204 and the solid electrolyte material 100 contained in the positive electrode active material layer may be, for example, 30% or more and 95% or less. When the volume ratio is 30% or more, the energy density of the battery can be sufficiently ensured. Also, when the volume ratio is 95% or less, there is a possibility that operation at high output will become easier.

[0068] The thickness of the electrolyte layer 202 may be, for example, 1 μm or more and 100 μm or less. If the thickness of the solid electrolyte layer is 1 μm or more, it is possible to suppress a short circuit between the positive electrode 201 and the negative electrode 203. Furthermore, if the thickness of the solid electrolyte layer is 100 μm or less, it is possible that high-output operation will be easier.

[0069] The negative electrode active material 205 is composed of a material having a property capable of absorbing and releasing metal ions such as lithium ions. Specifically, a metal material, a carbon material, etc. are used as the negative electrode active material 205. The metal material may be a simple metal or an alloy. Examples of the metal material include lithium metal and lithium alloys. Examples of the carbon material include natural graphite, coke, partially graphitized carbon, carbon fiber, spherical carbon, artificial graphite, and amorphous carbon.

[0070] The average particle size of the negative electrode active material 205 may be, for example, 0.1 μm or more and 100 μm or less. When the average particle size of the negative electrode active material 205 is 0.1 μm or more, the negative electrode active material 205 and the solid electrolyte material 100 may form a good dispersion state in the negative electrode active material layer. This can suppress the deterioration of the charge and discharge characteristics of the battery. In addition, when the average particle size of the negative electrode active material 205 is 100 μm or less, lithium diffusion in the negative electrode active material 205 does not become too slow, and the battery may operate more easily at high output.

[0071] The average particle size of the negative electrode active material 205 may be larger than the average particle size of the solid electrolyte material 100. This allows the negative electrode active material 205 and the solid electrolyte material to be well dispersed in the negative electrode active material layer.

[0072] The volume ratio of the negative electrode active material 205 to the total volume of the negative electrode active material 205 and the solid electrolyte material 100 contained in the negative electrode active material layer may be, for example, 30% or more and 95% or less. When the volume ratio is 30% or more, the energy density of the battery can be sufficiently ensured. Also, when the volume ratio is 95% or less, there is a possibility that operation at high output will become easier.

[0073] At least one of the positive electrode 201 and the negative electrode 203 may contain a conductive assistant as necessary. The conductive assistant is used to reduce the electrical resistance of the battery. Examples of the conductive assistant include graphites such as natural graphite and artificial graphite, and carbons such as acetylene black and ketjen black. The higher the electronic conductivity of the solid electrolyte 100 contained in the positive electrode 201 and the negative electrode 203, the smaller the amount of conductive assistant can be added, and the larger the proportion of the active material, the higher the energy density. EXAMPLES

[0074] The present disclosure will be described in more detail below with reference to examples, but the present invention is not limited to these.

[0075] Comparative Example 1 The raw material Li is dried in a dry atmosphere with a dew point of -50℃ or less. 2 S, P 2 S 5 , LiCl, and LiBr in a molar ratio of Li 2 S:P 2 S 5The mixture was weighed out so that the ratio of LiCl to LiBr was 3.8:1:2:1.2. These were pulverized and mixed in an absolute mill to obtain a mixture. The obtained mixture was filled into a crucible and placed in a sealed container made of quartz. A carbon packing was placed in the sealed container and tightened with a torque of 3 Nm. The sealed container was heat-treated at 500°C for 8 hours in a nitrogen atmosphere to obtain a powder of the solid electrolyte material of Comparative Example 1. This solid electrolyte material is Li 5.4 P.S. 4.4 Cl 1.0 Br 0.6 The composition was expressed by:

[0076] Comparative Example 2 The solid electrolyte material obtained in Comparative Example 1 and dehydrated heptane, which is liquid under standard conditions, were mixed in a mass ratio of Li 5.4 P.S. 4.4 Cl 1.0 Br 0.6 The mixture was mixed in a mortar at a ratio of 8:2:1 with hexane and dehydrated heptane, and the resulting mixture was filled in a crucible and placed in an alloy sealed container. An alloy O-ring was placed in the sealed container and tightened with a torque of 5 Nm. The sealed container was heat-treated at 500°C for 3 hours in a nitrogen atmosphere to obtain a powder of the solid electrolyte material of Comparative Example 2.

[0077] (Reference example) A powder of a solid electrolyte material of a reference example was obtained in the same manner as in Comparative Example 1, except that the heat treatment temperature was changed to 700°C.

[0078] Example 1 A powder of the solid electrolyte material of Example 1 was obtained in the same manner as in Comparative Example 2, except that the carbon source was changed to hexatriacontane.

[0079] Example 2 A powder of a solid electrolyte material of Example 2 was obtained in the same manner as in Example 1, except that the carbon source was changed to cyclododecane.

[0080] Example 3 A powder of a solid electrolyte material of Example 3 was obtained in the same manner as in Example 1, except that the carbon source was changed to eicosane.

[0081] Example 4 A powder of the solid electrolyte material of Example 4 was obtained in the same manner as in Example 1, except that the carbon source was changed to β-carotene.

[0082] Example 5 A powder of a solid electrolyte material of Example 5 was obtained in the same manner as in Example 4, except that the mass ratio of the solid electrolyte material to the carbon source was changed to 9:1.

[0083] Example 6 A powder of a solid electrolyte material of Example 6 was obtained in the same manner as in Example 4, except that the mass ratio of the solid electrolyte material to the carbon source was changed to 98:2.

[0084] <Evaluation> (Crystal structure analysis) The crystal structure of the solid electrolyte material was analyzed by measuring the X-ray diffraction pattern of a sample packed in a sealed cell at a dew point of -50°C using an X-ray diffractometer (RIGAKU Corporation, SmartLab). CuKα rays with wavelengths of 0.15405 nm and 0.15444 nm were used as the X-ray source. Figure 2 shows the X-ray diffraction pattern for Example 1, Figure 3 shows the X-ray diffraction pattern for the Reference Example, and Figure 4 shows the X-ray diffraction pattern for Comparative Example 1.

[0085] In Figure 2, Li 5.4 P.S. 4.4 Cl 1.0 Br 0.6 As main peaks derived from lithium halide, peaks were confirmed at 2θ=17.9°, 25.5°, 30.0°, 31.3°, and 44.9°. In addition, in FIG. 3, the solid electrolyte material of the reference example was partially decomposed due to the high firing temperature, and the peak intensity of impurities thought to be derived from lithium halide solid solution increased in the region of 33° to 35°. Therefore, the ionic conductivity of the reference example was about 1 / 12 of that of Comparative Example 1. The maximum intensity in the region of 29.5≦2θ≦30.5 was set as X A , the maximum intensity in the region of 33.5 ≦ 2θ ≦ 34.5 is X B When X B / X AThe value was 0.0074 for Example 1 and 0.12 for the Reference Example.

[0086] (Electronic conductivity measurement) The solid electrolyte materials produced in Comparative Examples 1-2 and Examples 1-6 were filled into a tablet molding machine, and a pressure of 309 MPa (pressure display value 3 tons) was applied using a mini press machine to produce a molded body for measurement (diameter about 11 mm, thickness 0.1-0.2 cm). The electronic conductivity of this molded body was measured by DC electrical measurement. The electronic conductivity value was measured at 25°C. The electronic conductivity was measured from the current value when a voltage of 1 V was applied for 30 minutes. The results are shown in Table 1.

[0087] (Raman spectrum measurement) The Raman spectrum was measured using a Raman spectrometer (Nanophoton Corporation, RAMANTouch) under the following conditions: -1 The maximum intensity near the G band peak intensity I G , 1350cm -1 The maximum intensity near the peak intensity I of the D band D , 415cm -1 More than 430cm -1 The maximum intensity below is the peak intensity I A , 2000cm -1 More than 4000cm -1 The maximum intensity in the following range is the impurity peak intensity I B The results are shown in Table 1.

[0088] - Raman spectrum measurement conditions - Laser wavelength: 532nm Laser intensity: 0.1mW or more Neutral density filter: 5% Slit width: 50μm Measurement range: 110cm -1 ~4340cm -1 Exposure time: 3 seconds Number of times: 5 Baseline correction method: Spline

[0089] [Table 1]

[0090] I G / I D is thought to represent the degree of graphitization of the attached carbon, and for the same amount of attached carbon, it is expected that the higher this value is, the higher the electronic conductivity will be. G / I A is considered to be an index of the amount of graphite in the solid electrolyte material, and I B / I A is considered to be an index representing the proportion of impurities contained in the solid electrolyte material.

[0091] Although the present disclosure is not bound by any theory, the dehydrated heptane of Comparative Example 2 is liquid under normal conditions and highly volatile. Therefore, it volatilizes during the production of the solid electrolyte material, for example, during mixing of the raw materials or during the heat treatment process, and the amount of the carbon source decreases, resulting in the formation of I G / I A It is believed that the use of solid carbon under standard conditions as the carbon source makes it possible to impart electronic conductivity to the solid electrolyte using a small amount of carbon source and a simple process.

[0092] (Preparation of positive electrode mixture) The positive electrode material is LiNi 0.60 Co 0.20 Mn 0.20 O 2 70 parts by mass of the above, 30 parts by mass of the solid electrolyte materials obtained in Examples 1 to 4 and Comparative Example 1, and 1 part by mass of VGCF (registered trademark) as a conductive assistant were mixed to obtain positive electrode composites for each of the Examples and Comparative Examples.

[0093] (Assembling the evaluation battery) A cylindrical lower mold having an outer diameter of 11 mm was inserted from the bottom of the outer mold into a cylindrical outer mold having an inner diameter of 11 mm. The upper end of the lower mold was fixed to a position in the middle of the outer mold. In this state, 100 mg of the solid electrolyte material obtained in Example Comparative Example 1 was poured into the upper end of the lower mold from the upper part of the outer mold. After pouring, a cylindrical upper mold having an outer diameter of 11 mm was inserted from the top of the outer mold. After insertion, a pressure of 50 MPa was applied from above the upper mold to mold the solid electrolyte material to form a solid electrolyte layer. After molding, the upper mold was pulled out from the top of the outer mold, and 20 mg of the above positive electrode mixture was poured into the top of the solid electrolyte layer from the top of the outer mold. After pouring, the upper mold was inserted again, and this time a pressure of 600 MPa was applied to mold the positive electrode mixture to form a positive electrode active material layer. After molding, the upper mold was fixed, the lower mold was released from its fixing and pulled out from the bottom of the outer mold, and the negative electrode active material LiAl alloy was poured into the bottom of the solid electrolyte layer from the bottom of the lower mold. After the charging, the lower die was inserted again and a pressure of 50 MPa was applied from below the lower die to mold the negative electrode active material into a negative electrode active material layer. The lower die was fixed in place while the pressure was applied, and a positive electrode terminal was attached to the upper die and a negative electrode terminal to the lower die to obtain an all-solid-state secondary battery for evaluation.

[0094] (Charge / discharge evaluation) The fabricated evaluation battery was charged and discharged at 2.2 V to 4.0 V using a charge / discharge tester (TOSCAT-3100, manufactured by Toyo Systems Co., Ltd.). The discharge current was set to the current value when 0.1 C capacity was extracted, and after the set voltage was reached, a current was passed to keep the voltage constant. The charge / discharge was terminated when the current value reached the equivalent of 0.02 C. The obtained charge capacity, discharge capacity, and charge / discharge efficiency are shown in Table 2.

[0095] [Table 2]

[0096] Batteries using a solid electrolyte material with high electronic conductivity as the positive electrode mixture showed larger charge / discharge capacity and higher coulombic efficiency.

[0097] Embodiments of the present disclosure include the following: [Section 1] Mixing a sulfide containing lithium, phosphorus, and sulfur and having an argyrodite-type crystal structure with a carbon source that is solid at a standard state to obtain a mixture; heat treating the mixture at a temperature of 400° C. or more and 550° C. or less; A method for producing a solid electrolyte material comprising the steps of: [Section 2] Item 2. The method for producing a solid electrolyte material according to item 1, wherein a mixing ratio of the sulfide to the carbon source is within a range of 100:1 to 60:40 by mass ratio. [Section 3] Item 3. The method for producing a solid electrolyte material according to item 1 or 2, wherein the carbon source is a hydrocarbon. [Section 4] Item 4. The method for producing a solid electrolyte material according to Item 3, wherein the carbon source does not have a double bond in its structure. [Section 5] A sulfide containing lithium, phosphorus, and sulfur and having an argyrodite-type crystal structure, at least a portion of which contains a carbon material, and having a peak intensity of the D band measured by Raman spectroscopy of I D , the G band peak intensity is I G , 415cm -1 More than 430cm -1 The peak intensity in the following region is I A When I G / I D is 0.8 or more, and I G / I A The argyrodite-type sulfide solid electrolyte material has a resistance of 0.07 or more. [Section 6] Raman spectroscopy at 1800 cm -1 More than 4000cm -1 The maximum intensity in the following region is I B When I B / I A Item 6. The argyrodite-type sulfide solid electrolyte material according to item 5, wherein the argyrodite-type sulfide solid electrolyte material has a molecular weight of 0.20 or less. [Section 7] I B / I A Item 7. The argyrodite-type sulfide solid electrolyte material according to item 6, wherein the argyrodite-type sulfide solid electrolyte material has a molecular weight of 0.05 or less. [Section 8] IG / I D 8. The argyrodite-type sulfide solid electrolyte material according to any one of items 5 to 7, wherein the value is 1.0 or more. [Section 9] In the diffraction pattern obtained by measurement using the X-ray diffraction method, the maximum intensity in the region of 29.5≦2θ≦30.5 is defined as X A , the maximum intensity in the region of 33.5 ≦ 2θ ≦ 34.5 is X B When X B / X A Item 9. The argyrodite-type sulfide solid electrolyte material according to any one of items 5 to 8, wherein Mn is ≦0.01. [Section 10] Item 10. A positive electrode mixture or a negative electrode mixture comprising the argyrodite-type sulfide solid electrolyte material according to any one of items 5 to 9.

Claims

1. Mixing a sulfide containing lithium, phosphorus, and sulfur and having an argyrodite-type crystal structure with a carbon source that is solid at a standard state to obtain a mixture; heat treating the mixture at a temperature of 400° C. or more and 550° C. or less; A method for producing a solid electrolyte material comprising the steps of:

2. 2. The method for producing a solid electrolyte material according to claim 1, wherein a mixing ratio of the sulfide to the carbon source is within a range of 100:1 to 60:40 in terms of mass ratio.

3. The method for producing a solid electrolyte material according to claim 1 , wherein the carbon source is a hydrocarbon.

4. The method for producing a solid electrolyte material according to claim 3 , wherein the carbon source is a saturated hydrocarbon.

5. A sulfide containing lithium, phosphorus and sulfur and having an argyrodite type crystal structure, at least a part of which contains a carbon material, and having a peak intensity of D band measured by Raman spectroscopy of I D , the G band peak intensity is I G , 415 cm -1 More than 430cm -1 The peak intensity in the following region is I A When I G / I D is 0.8 or more, and I G / I A The argyrodite-type sulfide solid electrolyte material has a melting point of 0.07 or more.

6. Raman spectroscopy at 1800 cm -1 More than 4000cm -1 The maximum intensity in the following region is I B When I B / I A The argyrodite-type sulfide solid electrolyte material according to claim 5, wherein the argyrodite-type sulfide solid electrolyte material has a molecular weight of 0.20 or less.

7. I B / I A The argyrodite-type sulfide solid electrolyte material according to claim 6, wherein the argyrodite-type sulfide solid electrolyte material has a molecular weight of 0.05 or less.

8. I G / I D The argyrodite-type sulfide solid electrolyte material according to claim 5, wherein the argyrodite-type sulfide solid electrolyte material has a molecular weight of 1.0 or more.

9. In the diffraction pattern obtained by measurement using an X-ray diffraction method, the maximum intensity in the region of 29.5≦2θ≦30.5 is defined as X A , the maximum intensity in the region of 33.5≦2θ≦34.5 is X B When this is done, X B / X A The argyrodite-type sulfide solid electrolyte material according to claim 5, wherein the argyrodite-type sulfide solid electrolyte material has a molecular weight of ≦0.

01.

10. A positive electrode mixture or a negative electrode mixture comprising the argyrodite-type sulfide solid electrolyte material according to any one of claims 5 to 9.

Citation Information

Patent Citations

  • Method for producing carbon-coated solid electrolyte particle

    JP2020135947A

  • Solid electrolyte material, solid cell, and method for manufacturing solid electrolyte material

    WO2012164724A1

Cited By

  • Positive electrode active material, positive electrode mixture, and solid-state battery

    WO2026211456A1